Fiziologija ledvic - Rupnik, Marjan (Medicinski razgledi, 2005)
These chapter describes the normal kidney function. The emphasis is on the mass flow of salts, water and some other products of the metabolism through the kidney tubular system. The clirens and counter-current flow systems and their function in the urin formation and the household of water are outlined.
Keywords: Kidney; Ledvica; Fiziologija; Physiology; Ledvični funkcijski testi; Kidney function tests; ledvice